Bridging the Knowledge Gap in Bangladesh for Effective Locally Driven Conditional Cash Transfer in Multisectoral Nutrition Programming. (7th June 2021) - Hasib, Enam; Joarder, Taufique; Nugroho, Kharisma; Perry, Kelly; Crum, Jennifer; Weissman, Amy
Abstract: Objectives: The USAID's Strengthening Multisectoral Nutrition Programming through Implementation Science Activity (MSNP) in Bangladesh gathered local knowledge to augment national data to ensure nutrition programming delivery was appropriately targeted. Such knowledge allowed MSNP's social protection conditional cash transfer (CCT) activity to reach most at-risk individuals. Methods: Using structured field observation forms, six trained staff documented nutrition programming decision-making processes and MSNP project activities regarding appropriate beneficiary targeting in six districts. Numerous project documents were reviewed and site visits conducted to evaluate CCT implementation in action. Data were coded into three aspects of learning (challenges and methods to alleviate them, successes, and recommendations for future programming) and analyzed according to themes identified in research utilization literature. Results: CCT, an incentive-based delivery mechanism targeting women based on locally collected data, positively influenced household decision-makers, including women, to provide effective health and nutrition care for themselves and their children. CCT, received upon completion of antenatal care visits and participation in nutrition education sessions, effectively supported the uptake of MSNP community workers' nutrition advice led to improve water, sanitation, and hygiene practices in remote areas. Requiring CCT beneficiaries to open bKash accounts to ensure financial transparency and that funds reached the intended participants helped establish women as nutrition decision makers, improving financial inclusion for extreme-poor women. Conclusions: CCT stimulates use of nutrition and health services, increasing household resources for nutrition-related behaviors and allowing women to exercise financial freedom. To improve evidence utilization in nutrition programming, national indicators must be complemented with local knowledge gathering processes, with local stakeholders and beneficiaries involved to ensure appropriate targeting and to transform knowledge into practice. Funding Sources: United States Agency for International Development (USAID).